Multi‐level analysis of the learning health system: Integrating contributions from research on organizations and implementation - Michael I. Harrison; Stephen M. Shortell (Wiley, 2021)
Abstract Introduction Organizations and systems that deliver health care may better adapt to rapid change in their environments by acting as learning organizations and learning health systems (LHSs). Despite widespread recognition that multilevel forces shape capacity for learning within care delivery organizations, there is no agreed‐on, comprehensive, multilevel framework to inform LHS research and practice. Methods We develop such a framework, which can enhance both research on LHSs and practical steps toward their development. We draw on existing frameworks and research within organization and implementation science and synthesize contributions from three influential frameworks: the Consolidated Framework for Implementation Research, the social‐ecological framework, and the organizational change framework. These frameworks come, respectively, from the fields of implementation science, public health, and organization science. Results Our proposed integrative framework includes both intraorganizational levels (individual, team, mid‐management, organization) and the operating and general environments in which delivery organizations operate. We stress the importance of examining interactions among influential factors both within and across system levels and focus on the effects of leadership, incentives, and culture. Additionally, we indicate that organizational learning depends substantially on internal and cross‐level alignment of these factors. We illustrate the contribution of our multilevel perspective by applying it to the analysis of three diverse implementation initiatives that aimed at specific care improvements and enduring system learning. Conclusions The framework and perspective developed here can help investigators and practitioners broadly scan and then investigate forces influencing improvement and learning and may point to otherwise unnoticed interactions among influential factors. The framework can also be used as a planning tool by managers and practitioners.